Evaluasi Kinerja Pegawai Negeri Sipil Dalam Meningkatkan Pelayanan Publik Di Kantor Camat Tompaso Kabupaten Minahasa - Lumentah, Jeferson Glandy; Posumah, Jhonny Hanny; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Sub-district as a public service agency has a duty to provide services to the public, so that the Civil Service will also determine the success of the public service. This research is to answer how the performance of the Civil Service to Improve Public Services Head office Tompaso Minahasa,This study uses a qualitative method. In this case the performance indicators used are productivity, kaualitas service, responsiveness, renponsibilitas, and accountability. Informants in this study were taken from the community, the old law, and an employee at the office of Head Tompaso (7 people), Law Tua (4 people), and people (5 people) of data collection by interview: while the analysis of data using analysis techniques interactive model of Miles and Huberman. The results showed: (1) The level of productivity is quite good views from the successful implementation of programs and activities that have been set. (2) Quality of service is pretty good views of the coordination of the Civil Service in providing services easy, fast, transparancy, and means. (3) The level of responsiveness is quite good, in response to all the needs and complaints of the public. (4) Level of Responsibility quite well, judging from the utilization of human resources potential of the Civil Service. (5) Level of Accountability pretty good views of the accountability system is done either to local governments and to the public. Based on the results of these studies conclude that the Civil Service Performance Evaluation In Improving Public Services Head office Tompaso Minahasa pretty good views of the productivity aspect, Quality service, Responsiveness, Responsibility, and Accountability. Keywords: Performance Evaluation of Civil Servants.